2013
DOI: 10.1111/epi.12187
|View full text |Cite
|
Sign up to set email alerts
|

Is routine electroencephalography (EEG) a useful biomarker for pharmacoresistant epilepsy?

Abstract: SUMMARYPeople with seizure disorders who have been treated at the Kork Epilepsy Center over a prolonged time period and who thus provide data concerning the chronic course of epilepsy were investigated in order to address the potential role of electroencephalography (EEG) as a biomarker for pharmacoresistant epilepsy. Clinical course and the corresponding findings from their first recorded EEG, their first EEG following appropriate treatment, and their last EEG were compared. Furthermore, we investigated if in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…However, seizure control was not associated with significantly different network patterns in our cohort and might not be a sensitive marker in a rather well controlled cohort. Similarly, persistent GSWD do not necessarily have an effect on long-term seizure prognosis 46 . Moreover, patients with higher medication load had lower connectivity in the beta1 frequency band.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, seizure control was not associated with significantly different network patterns in our cohort and might not be a sensitive marker in a rather well controlled cohort. Similarly, persistent GSWD do not necessarily have an effect on long-term seizure prognosis 46 . Moreover, patients with higher medication load had lower connectivity in the beta1 frequency band.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, persistent GSWD do not necessarily have an effect on long-term seizure prognosis. 46 Moreover, patients with higher medication load had lower connectivity in the β1 frequency band. Because only 6 patients received more than 2 antiepileptic agents at the time of the study, we can only speculate about a network downregulation through antiepileptic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patient studies found that IIS do not consistently correspond with disease activity (e.g., occurrence in relation to seizures or changes in anti-seizure medication levels) [11][12][13][14][15] . However, recent work in animals has identified unique aspects of IIS that correspond with experimental epileptogenesis [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…There is a report that EEGs are non-sufficient biomarkers for the prediction of pharmacoresistant epilepsy. Additional factors such as etiology and pathophysiology should also be taken into consideration [ 103 ]. Since neurophysiological and imaging tools have been rapidly improved, new epilepsy biomarkers employing such tools may be developed in the coming years and become clinical routine [ 42 ].…”
Section: Future Prospects On Development Of Rat Models For Epilepsy Rmentioning
confidence: 99%